Gene transfer and expression in mammalian cells - Makrides, Savvas C. (New comprehensive biochemistry, 2003)
The production of proteins in mammalian cells is an important tool in numerous scientific and commercial areas. For example, proteins for human therapy, vaccination or diagnostic applications are typically produced in mammalian cells. Gene cloning, protein engineering, biochemical and biophysical characterization of proteins also require the use of gene expression in mammalian cells. Other applications in widespread use involve screening of libraries of chemical compounds in drug discovery, and the development of cell-based biosensors. This book presents a state-of-the-art comprehensive coverage of the technical aspects of gene expression in mammalian cells, written by experienced scientists working at the forefront of the field.